Manipulating Interfacial Stability via Preferential Absorption for Highly Stable and Safe 4.6 V LiCoO2 Cathode - Chen, Long; He, Xin; Chen, Yiqing; Hou, Youmin; Zhang, Yujie; Wang, Kangli; Ai, Xinping; Cao, Yuliang; Chen, Zhongxue (Nano-Micro Letters, 2025)
Elevating the upper cutoff voltage to 4.6 V could effectively increase the reversible capacity of LiCoO2 (LCO) cathode, whereas the irreversible structural transition, unstable electrode/electrolyte interface and potentially induced safety hazards severely hinder its industrial application. Building a robust cathode/electrolyte interface film by electrolyte engineering is one of the efficient approaches to boost the performance of high-voltage LCO (HV-LCO); however, the elusive interfacial chemistry poses substantial challenges to the rational design of highly compatible electrolytes. Herein, we propose a novel electrolyte design strategy and screen proper solvents based on two factors: highest occupied molecular orbital energy level and LCO absorption energy. Tris (2, 2, 2-trifluoroethyl) phosphate is determined as the optimal solvent, whose low defluorination energy barrier significantly promotes the construction of LiF-rich cathode/electrolyte interface layer on the surface of LCO, thereby eventually suppresses the phase transition and enhances Li+ diffusion kinetics. The rationally designed electrolyte endows graphite||HV-LCO pouch cells with long cycle life (85.3% capacity retention after 700 cycles), wide-temperature adaptability (− 60–80 °C) and high safety (pass nail penetration). This work provides new insights into the electrolyte screening and rational design to constructing stable interface for high-energy lithium-ion batteries. Highlights: 1 A novel electrolyte design strategy for high voltage and high safe LiCoO2 (LCO) cathode based on highest occupied molecular orbital and LCO absorption energy descriptor was proposed. 2 The irreversible phase transformation was restricted by the LiF rich LCO/electrolyte interface. 3 The well designed tris 2, 2, 2-trifluoroethyl phosphate electrolyte endows Ah grade Gr||LCO pouch cell with excellent electrochemical performance (85.3% capacity retention after 700 cycles), low-temperature adaptability (−60 °C retention: 53%) and greatly improved thermal safety (pass nail penetration).